ANALISIS INOVASI KURIKULUM TAHFIZHUL QUR’AN DALAM MENINGKATKAN KUALITAS HAFALAN AL-QUR’AN SISWA DI MADRASAH - Nasution, Zulkipli (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
The quality of Al-Qur'an memorization of madrasah students is an important indicator of the success of education based on Islamic values. However, in practice, many educational institutions face obstacles such as weak tahfiz curriculum planning, monotonous methods, and lack of innovation in the learning process. This study aims to analyze the forms of innovation in the Tahfizhul Qur'an curriculum that can improve the quality of student memorization in madrasahs. This study uses a library research method by reviewing various academic literature, scientific journals, curriculum documents, and relevant previous research results. The results of the study show that innovation in the tahfiz curriculum can be seen from several main aspects: flexible and character-based curriculum planning, the application of varied learning strategies such as halaqah, visual methods, and digital technology, as well as a holistic evaluation system that involves parents. The innovative curriculum also emphasizes the importance of adjusting the memorization program to the individual abilities of students and strengthening spiritual values during the tahfiz process. In addition, the success of curriculum innovation is greatly influenced by the support of visionary madrasah leadership and participatory management. The implications of this study indicate that the development of an innovative tahfiz curriculum not only increases memorization achievement quantitatively, but also strengthens Islamic values in students as a whole. This study contributes to madrasah managers, tahfiz teachers, and policy makers in designing a more adaptive and meaningful tahfiz program.